Hubungan Kualitas Tidur, Durasi, dan Posisi Penggunaan Smartphone dengan Kejadian Asthenopia pada Mahasiswa Fakultas Kedokteran Universitas Islam Al-Azhar Angkatan 2022 - Maharani, Luh Gde Tri Cahya; Rahadianti, Dian; Apriliana, Denta Haritsa; Endro Pranoto (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Asthenopia or eye strain (eye strain) is a collection of symptoms related to vision, eye (ocular) and musculoskeletal problems. In Indonesia, as many as 60 million people suffer from eye problems, the number increasing by one million per year. This study aims to determine the relationship between sleep quality, duration and position of smartphone use with the incidence of asthenopia in students at the Faculty of Medicine, Al-Azhar Islamic University class of 2022. This research is a type of quantitative observational research using a cross sectional design. The sampling technique is total sampling. The research sample was 98 samples according to the inclusion and exclusion criteria. The data obtained were analyzed using the Spearman rank correlation test The results of this study showed that there were 40 respondents who experienced asthenopia (40.8%), and 58 respondents who did not experience asthenopia (59.2%). Respondents who had good sleep quality were 52 people (53.1%), respondents who had poor sleep quality were 46 people (46.9%). Respondents who used smartphones for a duration of 3-8 hours in one day were 48 people (49.0%), respondents who used smartphones for a duration of >8 hours in one day were 50 people (51.0%). Respondents who more often used smartphones in a sitting position were 58 people (52.9%), and respondents who more often used smartphones in a lying position were 40 people (40.8%). There is a relationship between sleep quality and the incidence of asthenopia with a p-value of 0.000 and a correlation coefficient of -0.800. There is a relationship between the duration of smartphone use and the incidence of asthenopia with a p-value of 0.000 and a correlation coefficient of 0.731. There is a relationship between the position of smartphone use and the incidence of asthenopia with a p-value of 0.000 and a correlation coefficient of 0.916. There is a significant relationship between sleep quality, duration and position of smartphone use and the incidence of asthenopia in students at the Faculty of Medicine, Al-Azhar Islamic University class of 2022.